Correlation Between Thrombus Signal Intensity and Aneurysm Wall Thickness in Partially Thrombosed Intracranial Aneurysms Using 7T Magnetization-Prepared Rapid Acquisition Gradient Echo Magnetic Resonance Imaging - Sato, Taku; Matsushige, Toshinori; Chen, Bixia; Gembruch, Oliver; Dammann, Philipp; Jabbarli, Ramazan; Forsting, Michael; Junker, Andreas; Maderwald, Stefan; Quick, Harald H.; Ladd, Mark E.; Sure, Ulrich; et al. (Frontiers in Neurology, 2022)
Objective The objective of this study is to investigate the relationship between the thrombus signal intensity and aneurysm wall thickness in partially thrombosed intracranial aneurysms in vivo with magnetization-prepared rapid acquisition gradient echo (MPRAGE) taken using 7T magnetic resonance imaging (MRI) and correlate the findings to wall instability. Methods Sixteen partially thrombosed intracranial aneurysms were evaluated using a 7T whole-body MR system with nonenhanced MPRAGE. To normalize the thrombus signal intensity, its highest signal intensity was compared to that of the anterior corpus callosum of the same subject, and the signal intensity ratio was calculated. The correlation between the thrombus signal intensity ratio and the thickness of the aneurysm wall was analyzed. Furthermore, aneurysmal histopathological specimens from six tissue samples were compared with radiological findings to detect any correlation. Results The mean thrombus signal intensity ratio was 0.57 (standard error of the mean [SEM] 0.06, range 0.25–1.01). The mean thickness of the aneurysm wall was 1.25 (SEM 0.08, range 0.84–1.55) mm. The thrombus signal intensity ratio significantly correlated with the aneurysm wall thickness (p < 0.01). The aneurysm walls with the high thrombus signal intensity ratio were significantly thicker. In histopathological examinations, three patients with a hypointense thrombus had fewer macrophages infiltrating the thrombus and a thin degenerated aneurysmal wall. In contrast, three patients with a hyperintense thrombus had abundant macrophages infiltrating the thrombus. Conclusion The thrombus signal intensity ratio in partially thrombosed intracranial aneurysms correlated with aneurysm wall thickness and histologic features, indicating wall instability.